Functional analysis of regenerated digit in newt following complete amputation at proximal interphalangeal joint - Takeshi KASAHARA; Machiko TERAMOTO; Kiyokazu AGATA; Jeonghyun KIM; Takeo MATSUMOTO; Eijiro MAEDA (Journal of Biomechanical Science and Engineering)
Amphibians possess high regeneration capacity of complicated structures such as articular joints. However, it is unknown when and how the joint function recovers during the regeneration process following a joint amputation. The present study examined the digit joint function in newt during regeneration process following complete amputation at its proximal interphalangeal (PIP) joint. The PIP joint of the hind middle digit of Iberian ribbed newt was amputated, and at several time points of the recovery period digit flexion test was performed to determine the relationship between mechanical loading applied to the flexor tendon and the flexion angle of PIP joints. There was a clear transition between 31 and 35 days post amputation (dpa) that the regenerated middle digit became flexible as the intact middle digit. The flexion of the PIP joint by mechanical loading at 28 dpa was significantly smaller than that of intact digits, and that of 31 dpa remained the same level. By contrast, the PIP joint flexion at 35 dpa was comparable to the intact digit. Histologically, the regenerated digit at 31 and 35 dpa showed no remarkable differences. Accordingly, potential mechanisms of regaining the flexion in the regenerated digit were that 1) the regenerated flexor tendon was reintegrated into the distal phalanx at 35 dpa, so that the pulling force from the flexor muscle generated sufficient torque to flex the regenerated PIP joint, 2) the regenerated PIP joint regained its interlocking structure and the flexibility was recovered to the intact level, or these mechanisms worked together.